Necessity of Tobramycin trough Levels in Once Daily Iv-Treatment in Patients with Cystic Fibrosis - Schlegtendal, Anne; Rettberg, Sophia; Maier, Christoph; Brinkmann, Folke; Koerner-Rettberg, Cordula (Klinische Pädiatrie, 2024)
Background Once daily intravenous (iv) treatment with tobramycin for Pseudomonas aeruginosa infection in patients with cystic fibrosis (pwCF) is frequently monitored by measuring tobramycin trough levels (TLs). Although the necessity of these TLs is recently questioned in pwCF without renal impairment, no study has evaluated this so far. The aim of this observational study was to evaluate the frequency of increased tobramycin TLs in pwCF treated with a once daily tobramycin dosing protocol.Methods Patient records of all consecutive once daily iv tobramycin courses in 35 pwCF between 07/2009 and 07/2019 were analyzed for tobramycin level, renal function, co-medication and comorbidity.Results Eight elevated TLs (2.9% of 278 courses) were recorded in four patients, two with normal renal function. One of these resolved without adjustment of tobramycin dosages suggesting a test timing or laboratory error. In the other patient the elevated tobramycin level decreased after tobramycin dosage adjustment. Six of the elevated levels occurred in two patients with chronic renal failure. In 15 other patients with reduced glomerular filtration rate (GFR) (36 courses) but normal range creatinine no case of elevated tobramycin trough levels was detected. Neither cumulative tobramycin dosages nor concomitant diabetes or nutritional status were risk factors for elevated TLs.Conclusion Our data show that elevated tobramycin TLs are rare but cannot be excluded, so determination of tobramycin TLs is still recommended for safety.
Keywords: tobramycin trough level; cystic fibrosis; GFR; renal insuffiency; toxicity; aminoglycoside